Prosthetic arm for industrial and medical field / Muhammad Lutfi Akmal Izaharuddin - Izaharuddin, Muhammad Lutfi Akmal In various fields, such as open surgery in (2024)
In various fields, such as open surgery in the medical domain and industrial work encompassing construction sites and factory operations, the demand for precision and accuracy is paramount. These professions entail tasks that require meticulous attention to detail, as even the slightest error can pose significant risks to individuals and those in proximity, including patients and coworkers. Unfortunately, the occurrence of injuries in these settings is often attributed to human error, stemming from factors like fatigue, diminished focus, tiredness, and the inevitable impact of age-related limitations. The perpetual challenge lies in addressing these human limitations, as they persist across generations without comprehensive solutions. The absence of a foolproof method to counteract the impact of human fallibility poses a substantial drawback in fields where precision is crucial. The repercussions of inadequate precision extend beyond individual practitioners, affecting the safety of patients, buyers, workers, and even the professionals themselves. Recognizing this pressing issue, our project endeavours to tackle the pervasive problem of human error by implementing precision control mechanisms. By doing so, our objective is to create a secure working environment that mitigates the inherent risks associated with these high-stakes tasks. The proposed system aims to eradicate human error, thereby ensuring that operations can be conducted with enhanced safety measures and a significant reduction in the potential for injuries. Through the implementation of this innovative solution, we aspire to revolutionize the approach to precision-dependent tasks, fostering a safer and more reliable working environment for all stakeholders involved